Barriers to, and Facilitators of Physical Activity in Patients Receiving Chemotherapy for Lung Cancer: An exploratory study. Issue 2 (June 2015) - Mas, Sébastien; Quantin, Xavier; Ninot, Grégory
Aim: Physical activity (PA) has a positive effect on the cardiorespiratory fitness, lung cancer symptoms, and quality of life of lung cancer patients. The aim of our study was to identify barriers to, and facilitators of PA in lung cancer patients. Methods: We collected data from five patients diagnosed with primary, advanced non-small-cell lung cancer (NSCLC) who were receiving chemotherapy. Choosing a qualitative approach, we conducted an exploratory analysis using the thematic analysis technique to process the data. Results: Seven barriers to, and facilitators of PA were identified and grouped into four categories. We found that psychological and social factors affect patients' willingness and ability to engage in PA, while physiological and environmental factors have an impact on the duration, intensity, and regularity of their PA. Conclusion: Our study highlighted some of the effects that the barriers to PA have on the practice of it in our patient group. Our findings may be used by professionals to design adapted PA programs.